Optimalisasi Kenyamanan Termal Rumah Tinggal Bali Kontemporer di Kabupaten Gianyar - I Made Krishna Aryasutha; I Putu Weka Wendyputra; Ni Made Yudantini; Try Ramadhan (Universitas Sebelas Maret Surakarta, 2024)
Thermal comfort is an important aspect to achieve in residential buildings. Therefore, this research aims to optimize thermal comfort in residential buildings with Contemporary Balinese Architecture in one of the high-density areas in Bali, namely Gianyar Regency. This study aims to provide design strategy solutions through a descriptive quantitative method in the form of building model simulations using Autodesk Ecotect Analysis software. The optimization focuses on openings and the use of solar reflective paint on the building's exterior to achieve an optimal level of thermal comfort. The results of the case study show that the addition of openings and the use of solar reflective paint can help improve thermal comfort by reducing the MRT (Mean Radiant Temperature) in the building by 0.96°C. The PMV (Predicted Mean Vote) and PPD (Predicted Percentage of Dissatisfied) indices were also successfully improved compared to the existing conditions.